PENGARUH DISIPLIN KERJA DAN PENILAIAN PRESTASI KERJA TERHADAP KINERJA KARYAWAN PADA PT EPCOS INDONESIA DI BATAM - Bakara, Nova Damauli; Afridola, Sri (SCIENTIA JOURNAL, 2019)
This learning instend determine the influence assessment on employe performance. This study used quantitative approach, research method that intends to provide explanation of relationship and influence between variables. The population in this study are employee of the relationship and influence between variables. The population in this study are employees PT. Epcos Indonesia in Batam, amounting 700 people. Samples were taken using random sampling 40% of populations, so that 280 samples were optained, then processed using SPSS 20 assistend with computer media. The test used in this study is validity test, reliability test, classic asumsi test, multiple linear regression test and hypothesis test. From the results of the test result showed the work discipline had significant and positive effect employee performance bassed on result test thitung > ttabel (8,708 > 1,968565) with significance value 0,000 < 0,005. Assessment work performance has significant and positive effect on employee perfofmance bassed on the result the test thitung > ttabel (4,013 > 1,968565) with asignificance value of 0,000 > 0,005, furthermore, from the test result this study work discipline and work performance assessment together have Fhitung > Ftabel (73,580 > 3,028) and significant value 0,000 < 0,005.